Clinical and Genetic Characteristics of Mitochondrial Encephalopathy Due to FOXRED1 Mutations: Two Chinese Case Reports and a Review of the Literature - Hu, Chaoping; Xu, Qiong; Shen, Jin; Wang, Yi (Frontiers in Neurology, 2021)
Background As one of the assembly factors of complex I in the mitochondrial respiratory chain, FOXRED1 plays an important role in mitochondrial function. However, only a few patients with mitochondrial encephalopathy due to FOXRED1 defects have been reported. Methods Two Chinese patients with mitochondrial encephalopathy due to mutations in FOXRED1 were identified through trio whole-exome sequencing. The clinical presentation, laboratory data, brain imaging findings, and genetic results were collected and reviewed. All previously reported cases with FOXRED1-related mitochondrial encephalopathy were collected using a PubMed search, and their data were reviewed. Results Two patients presented with severe neurodevelopmental delay, epilepsy, and high lactic acid levels, as well as remarkable diffuse brain atrophy and polycystic encephalomalacia during early infancy. Trio whole-exome sequencing revealed compound heterozygous variants in both patients: one case harbored a c.606_607delAG frame-shift variant and a c.1054C>T (p.R352W) variant, while the other carried a novel c.352C>T (p.Q118X) variant and a reported c.1054C>T (p.R352W) variant. To date, 9 patients have been reported with FOXRED1 defects, including our two cases. The most common presentations were neurodevelopment delay (100%), epilepsy (80%), poor feeding (30%) and vision loss (20%). Multisystem involvement comprised cardiovascular dysfunction (30%), abnormal liver function (20%) and hypoglycemia (10%). The neuroimaging results ranged from normal to severe cerebral atrophy and polycystic encephalomalacia in early infancy. Eleven pathogenic variants in FOXRED1 have been reported, comprising six missense variants, two nonsense variants, two frameshift variants, and one splice variant, among which the c.1054C>T (p.R352W) and c.612_615dupAGTG (p.A206SfsX15) variants are more common. Conclusion FOXRED1-related mitochondrial disorders have high clinical and genetic heterogeneity. Our study expanded the clinical and genetic spectrum of FOXRED1 defects. Early infantile onset and progressive encephalopathy are the most common clinical presentations, while the variants c.1054C>T (p.R352W) and c.612_615dupAGTG (p.A206SfsX15) may be critical founder mutations.